Novel compound heterozygous mutations of ECM1 in a Chinese family with lipoid proteinosis - Wei Wu; Jian-Qiang Shi; Ding Li; Fang-Gu Li; Yan-Xia Cai; Di-Qing Luo (Wolters Kluwer Medknow Publications, 2019)
Lipoid proteinosis (LP) is a rare autosomal recessive genodermatosis caused by mutations of the ECM1 gene. The common variations of the ECM1 gene are nonsense and missense mutations, and in rare instance, compound heterozygotes may occur. We describe two siblings of LP from a nonconsanguineous family of China who were detected novel compound heterozygous mutations of c. 157C >T(p. R53X) in exon 3 and c. 857G >A (p. C286Y) in exon 7 of the ECM1 gene. Their mother was a carrier of missense mutation of c. 857G >A in exon 7 of ECM1, their father and one of the old sisters were the carriers of nonsense mutation of c. 157C >T in exon 3, respectively. All the carriers presented normally. The results support the opinion that the mutations of the ECM1 gene for LP are of varieties.